Digital psychiatry in low- and middle-income countries post-COVID-19: Opportunities, challenges, and solutions - Naeem, Farooq (Indian J Psychiatry, 2020)
Health systems are adapting to the unique challenges posed by the COVID-19 pandemic. Social distancing has forced clinicians to provide their services through online platforms in high income countries. Similar trends have been noticed in Low and middle-income countries (LAMIC). Digital health can help LAMIC address traditional barriers to care by overcoming issues related to stigma, discrimination, staffing, and physical and geographical resource constraints. Mobile phone subscriptions exceed 80% of the population in many LAMICs. Mobile platforms represent a viable resource in overcoming the significant mental health gap in LAMIC. This paper discusses the enormous potential that digital health has to transform healthcare delivery in LAMICs, as well as numerous challenges to implementation. We also discuss the need to develop national digital health strategies and suggest solutions to some of the barriers.